2021
DOI: 10.1155/2021/5558890
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Electroacupuncture on Bladder Dysfunction via Regulation of MLC and MLCK Phosphorylation in a Rat Model of Type 2 Diabetes Mellitus

Abstract: Previous studies observed have reported that electroacupuncture (EA) is effective in relieving diabetic bladder dysfunction (DBD); however, little is known about the mechanism. Therefore, we explored the effects and mechanisms of EA on DBD in streptozotocin–high-fat diet- (STZ–HFD-) induced diabetic rats. The Sprague-Dawley male rats were divided randomly into four groups: normal group, diabetes mellitus group (DM group), DM with EA treatment group (EA group), and DM with sham EA treatment group (sham EA group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 58 publications
3
4
0
Order By: Relevance
“…The results showed that the T2DM rat model was successfully induced in this experiment, indicating that the current disease status in rats is like the pathophysiological state of human T2DM combined with DBD, which is consistent with our previous findings ( Han et al, 2021 ).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The results showed that the T2DM rat model was successfully induced in this experiment, indicating that the current disease status in rats is like the pathophysiological state of human T2DM combined with DBD, which is consistent with our previous findings ( Han et al, 2021 ).…”
Section: Resultssupporting
confidence: 92%
“…Consequently, these data suggest that unbalanced PACAP38 levels coupled with bladder remodeling may be a pathophysiological mechanism in DBD. Our previous study confirmed that EA could effectively alleviate bladder dysfunction in diabetic rats ( Han et al, 2021 ). Moreover, another study found that EA can regulate the urodynamics of neurogenic bladder model rats by up-regulating the protein expressions of PACAP38 and PAC1-R ( Liu et al, 2017 ).…”
Section: Discussionsupporting
confidence: 67%
“…As previously stated, neuropathy is one of the underlying causes of diabetes related bladder dysfunction. Neuromodulation was shown to restore voiding function in several studies (Chen et al 2013 ; Hsieh et al 2016 ; Han et al 2021 ). Voiding efficacy in control animals was found about 75% while it was measured as 30.02 ± 7.89% after 8 weeks of diabetes and 19.98 ± 6.03% after 18 weeks of diabetes in STZ-induced T1DM male rats (Chen et al 2013 ).…”
Section: Emerging Pathophysiology-based Treatments Of Lutd In Diabetesmentioning
confidence: 99%
“…All of the abnormalities were improved by electroacupuncture therapy and its beneficial effect was ascribed to regulation of myosin light chain and myosin light chain kinase phosphorylation. Moreover, electroacupuncture was reduced infiltration of inflammatory cells in bladder (Han et al 2021 ). These studies suggests that electrical stimulation of bladder may prevent or improve bladder dysfunction in diabetic individuals by facilitating bladder contraction.…”
Section: Emerging Pathophysiology-based Treatments Of Lutd In Diabetesmentioning
confidence: 99%
“…Bladder mucosa is composed of transitional epithelium (urothelium), basement membrane, and lamina propria (LP) [8]. Structural analysis has revealed that the LP contains a rich neurovascular network, elastic fibers, and smooth muscle bundles (muscularis mucosa) [8][9][10], and recent studies suggest that increased cellular degeneration and necrosis of bladder mucosal cells may underlie bladder microvascular and nerves damage in diabetes [11]. In addition, microvascular injury may impair bladder innervation, alter detrusor function, and lead to urothelial dysfunction [12].…”
Section: Introductionmentioning
confidence: 99%